A new wasp genus of Cirrosphecidae (Hymenoptera: Apoidea) from mid-Cretaceous amber of northern Myanmar. (December 2022) - Li, Longfeng; Rosa, Brunno B.; Melo, Gabriel A.R.; Shih, Chungkun; Ren, Dong
Abstract: A new apoid genus with one new species Heterosphex wuni Li, Rosa, Melo and Shih gen. et sp. nov. is described in Cirrosphecidae based on a male wasp from mid-Cretaceous Myanmar (Burmese) amber. The new taxon is placed in Cirrosphecidae due to its swollen, ring-like metanotum with anterior margin surrounding the scutellum; omaular sulcus and omaular carina absent; propodeum short, with rounded edges and distinctly slanted; metapostnotum extending as a narrow triangle onto posterior surface of propodeum; notaulus not indicated; claws with subapical teeth; and mid tibia with one spur. A key for genera and species of Cirrosphecidae is provided. Up to date, all taxa in Cirrosphecidae are known only from mid-Cretaceous Myanmar amber.